2021
DOI: 10.3389/fpsyt.2021.656646
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Child Maltreatment and Depressive Symptoms Among Chinese College Students: An Analysis of Sex Differences

Abstract: Background: Depressive symptoms and child maltreatment are both global public health problems among young adults. This study aimed to investigate the associations between five types of child maltreatment and depressive symptoms among Chinese college students, with a focus on potential sex differences.Methods: A cross-sectional study of a nationally representative sample of Chinese college students was conducted from March to June 2019 with a multistage, stratified cluster, random sampling method. In total, 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…A dichotomous variable of any childhood maltreatment was classified based on previous work (Chen et al, 2021 ): participants either experienced childhood maltreatment (i.e. participants reported at least moderate to severe cutoff scores in one of the subscales of CTQ) or did not experience childhood maltreatment (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A dichotomous variable of any childhood maltreatment was classified based on previous work (Chen et al, 2021 ): participants either experienced childhood maltreatment (i.e. participants reported at least moderate to severe cutoff scores in one of the subscales of CTQ) or did not experience childhood maltreatment (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This may be related to the individual and the exposure to different levels of CSA severity. In addition, a large study in China suggested a dose‒response relationship between the types of child abuse experienced and mental health [ 27 ]. It is evident that adverse childhood experiences are associated with mental health and are also likely to influence individual behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…If different levels of CSA severity affect premarital sex, are there sex differences in the effects? Only one study discovered that sex modifies the effects of CSA on health, implying that the effect of child maltreatment on the risk of depressive symptoms in college students is moderated by sex, with a greater effect in females than males [ 27 ]. However, it is unclear whether sex modifies the effect of CSA severity on premarital sex.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 32 studies, the pooled prevalence of childhood maltreatment among college students in China was 64.7% (95% CI: 52.3-75.6%) [ 13 ]. Exposure to childhood maltreatment may further increase severe mental health problems, including depression and anxiety symptoms, in early adulthood [ 14 16 ]. One study suggests that if childhood maltreatment were reduced by 10–25%, between 31.4 million and 80.3 million cases of depression and anxiety could potentially be prevented worldwide [ 17 ].…”
Section: Introductionmentioning
confidence: 99%